Statistical characterization of projected flooding and erosion processes for coastal management - Otiñar, Pedro; Cobos, Manuel; Santana, Marcus; Baquerizo, Asunción (Frontiers in Marine Science, 2025)
Despite significant scientific progress in developing long-term projections of coastal impacts and the growing concern of public authorities, the transfer of knowledge from academia to policy remains less effective than desired. As a result, the legal and administrative frameworks guiding coastal management are often misaligned with the latest scientific evidence. To help address this gap, we present a procedure for the stochastic characterization of erosion and flooding, aimed at supporting informed management decision-making using projections under a climate change scenario. The approach focuses on a comprehensive collection of random sets defined in accordance with the Spanish regulatory framework and the needs of the regional administrative authority responsible for granting permits and concessions for the use and/or occupation of land within the public maritime-terrestrial domain in Andalusia (Spain). The study analyses the spatial and temporal variability of these random sets in probabilistic terms across different time horizons. These time frames are introduced to harmonize the definitions and criteria established in legal texts with the mandate to account for climate change impacts. Statistical analyses are also conducted for both peak and off-peak tourist seasons, as well as on annual time scales, to support managerial decision-making based on the specific characteristics of the coastal management issues at hand, including their potential seasonal nature. The results, obtained for the provinces of Granada and Almería along the Mediterranean Andalusian coast for the high-emissions Representative Concentration Pathway scenario (RCP 8.5), underscore the importance of considering specific time horizons—and, when relevant, seasonal variability—when authorizing uses and concessions in coastal zones. In this regard, it was found that by 2100, 40% of beaches in the studied provinces are projected to lose over 80% of their dry beach area during the off-peak tourist season, with only 33% of them failing to recover by the tourist season. This highlights the importance of considering natural recovery capacities in coastal management to potentially avoid drastic interventions. Furthermore, the analysis reveals the high sensitivity of the parameters currently used in Spanish legislation to define the public maritime-terrestrial domain and to identify areas of severe coastal regression, along with their implications along the coastline.